Sample Profitability and Cost Estimates of Producing Sweet Flavored Carambola (Averrhoa carambola) in south Florida. - Fredy H Ballen; Edward Evans; Jonathan Crane; Aditya Singh (EDIS, 2020)
This 7-page fact sheet written by Fredy H. Ballen, Aditya Singh, Edward A. Evans, and Jonathan H. Crane and published by the UF/IFAS Food and Resource Economics Department reports the costs and returns of operating an established sweet-flavored carambola grove in south Florida. It is intended to provide a reference to help estimate the financial requirements of running an established grove. Information was collected through field interviews with growers and industry specialists about a wide range of production practices used on small farms of five acres or fewer